POLA SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM RANGKA MENINGKATKAN KINERJA GURU SEKOLAH MENENGAH ATAS MUHAMMADIYAH 3 YOGYAKARTA, TAHUN AJARAN 2012-2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2014)
The Principal Academic Supervision Pattern of Senior High School Muhammadiyah 3 Yogyakarta In Order To Improve Teacher’s Performance. This research is aimed to reveal the academic supervision pattern performed by the principal in order to improve techers performance, the obstacles on the academic supervision application, and to follow up the academic supervision application. This research used qualitative approach which is placed in Senior High School Muhammadiyah 3 Yogyakarta. The data source consist of the headmaster, the teachers, and administratration stafs. The research data was collected and compiled through observations, interviews, and documentations. The data was analyzed with analysis model through data reduction, data display, and conclusion drawing. The result of descriptive analysis explains that the academic supervision performed by the principal of Senior High School Muhammadiyah 3 Yogyakarta is continuously wellperformed, well-planned, well-programed, and well-scheduled. The academic supervision includes improving class-visit program, observing the lesson plans, and coordinating learning media and its application in the teaching learning process. Due to this academic supervision, the principal is proven to be able to improve teacher’s performance. The fact that teachers have performed well in the teaching-learning process in terms of planning, performing, evaluating, following-up, and problem solving supports the idea above. The main obstacle found in performing the academic supervision is the contradicting schedule. Contradicting schedule of suddent agendas often interrupts principal’s work in performing the academic supervision. It is hoped that principal is eager to work on this obstacle to achieve the ideal academic supervision performance.